PENGELOLAAN PROFESIONALISME GURU DI ERA REVOLUSI INDUSTRI 4.0 - Diyah Yuli Sugiarti (LPPM Universitas Islam 45, 2023)
In the current era of the 4.0 Industrial Revolution, providing many opportunities and challenges for teacher professionalism, competition in all fields is getting wider and tighter. The safe zone is no longer profitable amidst the turmoil of change. The profession of teachers is required to increase their professionalism in the midst of technological developments. This study aims to find out how the management of increasing teacher professionalism in the Industrial 4.0 era. This study uses a descriptive qualitative approach. The data was taken through observation and interviews with public elementary school teachers in the city of Bekasi. The results of the research show that the era of the Industrial Revolution 4.0 has opened awareness of the importance of increasing teacher professionalism, but so far the level of implementation is still far from expectations. The teaching profession is carried out as a routine. So it is necessary to increase the professionalism of teachers. To make this happen, it is necessary to manage teacher professionalism through: Increasing standardization, Plan, Do, Check, and Action to increase teacher professionalism that is relevant to the Industry 4.0 era. And this, of course, requires an education policy from the government, and it is carried out by related agencies to units of educational institutions.